Effect of Fly Ash on the Characteristics of Expansive Soils in Sudan - M. E. Zumrawi, Magdi; H. Mohammed, Mohammed (University of Khartoum Engineering Journal, 2022)
This paper discusses the effect of Fly ash on the engineering properties of expansive soils. As reviewed in literature, many previous investigations have shown promising results for improvement of expansive soil after stabilization with Fly ash. Laboratory tests have been conducted on expansive soils obtained from three different regions in Khartoum state. Various percentages of Fly ash such as 0%, 10%, 20%, 25%, and 30% by weight of soil were added to the three soils and their influence on the soil plasticity, swell characteristics and unconfined compression strength are discussed. Additions of Fly ash to the three soils resulted in significant improvement in the strength and reduction in plasticity and swell properties of soils. The unconfined compression strength of soils treated with 10% Fly ash showed almost 2 times improvement compared with untreated soils. For the addition of 10% fly ash, the reduction in free swell, swell pressure and swell potential is in the range 50% to 70%. Further addition of fly ash caused a reduction in the swell characteristics of 90% at 25% fly ash. Hence, it is concluded that the fly ash has a good potential to be used as a additive for improving the engineering properties of expansive soil.